Robotics for young children : STEM activities and simple coding - Gadzikowski, Ann (St. Paul, MN : Redleaf Press, 2017)
'This book offers ideas for introducing young children to both the building of and the programming of robots through playful, developmentally appropriate activities. Suggested materials include traditional toys like blocks and clay, household items like clocks and radios, and tech devices like tablets and robotics kits'--
Includes bibliographical references.
Keywords: Robotics -- Study and teaching (Early childhood) -- Activity programs